Performance and tolerance of the AL Bandeirantes maize cultivar to salt stress - Santos, Ricardo Gonçalves; Albuquerque, Cynthia Cavalcanti de; Paiva, Dayane Carla Costa; Oliveira, Francisco Fábio Mesquita; Ragagnin, Roberto Carlos Grillo; Cipriano, Aline Kelly de Aquino Lima (MAGISTRA, 2017)
The maize (Zea mays L., Poaceae) is a high productivity plant, but its agricultural yield is compromised in areas with soil salinity problems. This study aimed to evaluate the performance of maize plants (AL Bandeirantes cultivar) submitted to different levels of salinity. The experiment was conducted in greenhouse conditions under completely randomized design, with 4 treatments (0, 50, 100 and 150 mM of NaCl). An additional group of plants was not exposed to NaCl (controls). The plants were evaluated for height, root volume, shoot and root dry weight, shoot/root ratio, relative water content and proline concentration in leaves. The NaCl reduced the dry weight and the root volume in comparison with that observed for the control. The plants height was affected only after 21 days of exposure to salt stress, while no significant difference in relative water content was observed among treatments. The proline accumulation was expressive in the plants treated with 150 mM of NaCl, indicating a mechanism for regulating osmotic. Salt stress did not affect the survival of the AL Bandeirantes cultivar, as was observed by plants development at all concentrations applied.